2017
DOI: 10.3892/mmr.2017.7131
|View full text |Cite
|
Sign up to set email alerts
|

HPK1 positive expression associated with longer overall survival in patients with estrogen receptor-positive invasive ductal carcinoma-not otherwise specified

Abstract: Hematopoietic progenitor kinase 1 (HPK1) belongs to the mitogen activated protein kinase kinase kinase kinase (MAP4K) family of serine/threonine kinases, which have been associated with the incidence and progression of a variety of gastrointestinal malignant tumors in humans. However, the potential association between HPK1 expression and breast cancer, particularly invasive ductal carcinoma-not otherwise specified (IDC-NOS) development, has not yet been examined. To address this gap, the present study aimed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…However, the direct relationship between HPK1 expression and immune response needs further study. Nevertheless, HPK1 may be a new effective therapeutic target for IDC-NOS for further study …”
Section: Pathological Roles Of Hpk1 In Related Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the direct relationship between HPK1 expression and immune response needs further study. Nevertheless, HPK1 may be a new effective therapeutic target for IDC-NOS for further study …”
Section: Pathological Roles Of Hpk1 In Related Diseasesmentioning
confidence: 99%
“…Nevertheless, HPK1 may be a new effective therapeutic target for IDC-NOS for further study. 84 HPK1 is expressed in normal pancreatic ductal cells, but is absent in pancreatic ductal adenocarcinoma (PDAC). HPK1 is known to act as a negative feedback regulator of T cells, or as a regulator of the MAPK/ERK pathway.…”
Section: Pathological Roles Of Hpk1 In Related Diseasesmentioning
confidence: 99%
“…For example, Hematopoietic Progenitor Kinase-1 (HPK1) is a member of the MAP4K family expressed largely in hematopoietic cells [78], and acts upstream of MAPK signaling [79]. HPK1 has been reported to regulate both nuclear factor kappa-light-chain-enhancer of activated B cells (NFkB) and activates JNK signaling pathway [80], and is associated with progression of gastrointestinal tumors [81]. The roles of HPK1 in T-cell function is now becoming clear.…”
Section: Other Mapk Family Membersmentioning
confidence: 99%
“…Furthermore, Wang, J., et, al. reported that HPK1 positive expression associated with longer overall survival in patients with estrogen receptor-positive invasive ductal carcinoma [11]. MAP4K1 affected cell-cycle progression and mediated Vitamin D resistance in AML cell lines [12].…”
Section: Introductionmentioning
confidence: 99%